FOLFOXIRI and bevacizumab in patients with early-onset metastatic colorectal cancer. A pooled analysis of TRIBE and TRIBE2 studies. (May 2022) - Antoniotti, Carlotta; Germani, Marco M.; Rossini, Daniele; Lonardi, Sara; Pietrantonio, Filippo; Santini, Daniele; Marmorino, Federica; Allegrini, Giacomo; Daniel, Francesca; Raimondi, Alessandra; Borelli, Beatrice; Zaniboni, Alberto; et al.
Abstract: Background: We performed a pooled analysis of TRIBE and TRIBE2 studies to assess the efficacy and safety of the intensification of upfront chemotherapy backbone – from doublets to the triplet FOLFOXIRI – in combination with bevacizumab (bev) in patients with early-onset metastatic colorectal cancer (EO-mCRC; aged <50 years) and to explore whether EO-mCRCs have a peculiar tumour genomic profiling. Materials and methods: Subgroup analyses according to age (<50 versus ≥50 years) and treatment (FOLFOXIRI/bev versus doublets/bev) were carried out for rates of any grade and grade ≥3 (≥G3) overall and singular adverse events, progression-free survival (PFS), overall survival (OS) and objective response rate (ORR). Tumour genomic profiling was obtained using a DNA-based next-generation sequencing platform. Results: Of 1187 patients included, 194 (16%) patients were aged <50 years. Females were more frequently diagnosed with EO-mCRC ( P  = 0.04). Patients aged <50 years showed a lower risk of ≥G3 neutropenia ( P  = 0.07), diarrhoea ( P  = 0.04), asthenia (P = 0.008) and a higher risk of any grade nausea ( P  < 0.01) and vomiting ( P  < 0.01). Patients receiving FOLFOXIRI/bev more frequently experienced ≥G3 chemotherapy-related adverse events respect to doublets/bev, regardless of age ( P interaction  = 0.60). FOLFOXIRI/bev was associated to a lower incidence of neutropenia ( P  = 0.04) and asthenia ( P  = 0.01) in patients <50 years old, than those aged ≥50 years. PFS, OS and ORR did not differ according to age (PFS P  = 0.81, OS P  = 0.44, ORR P  = 0.50) and no interaction between age and the benefit from the intensification of upfront chemotherapy was observed (PFS P interaction  = 0.72, OS P interaction  = 0.54, ORR P interaction  = 0.65). Genomic profiling was assessed in 296 patients, showing an enrichment of FBXW7 and POLE mutations in EO-mCRC. Conclusions: Upfront FOLFOXIRI/bev shows a favourable efficacy/safety balance in EO-mCRC. Trial registration: Clinicaltrials.gov Identifiers NCT00719797, NCT0233-9116. Highlights: Early-onset metastatic colorectal cancer (EO-mCRC) – diagnosed < 50 years – is not related to poor prognosis. EO-mCRC does not have peculiar clinical and genomic features. The efficacy of upfront FOLFOXIRI/bev is similar in patients aged < and ≥50 years. FOLFOXIRI/bev is associated with a favourable safety profile in patients with EO-mCRC.